The Impact of Nutrition on Academic Performance: A Review of Evidence and Implications for Student Education (International Journal of Food and Nutritional Sciences, 2022)
This paper provides a comprehensive review of existing evidence regarding theimpact of nutrition on academic performance among students. The relationship betweennutrition and cognitive function has been extensively studied, and findings suggest that dietquality significantly influences various aspects of academic achievement, including cognitiveabilities, concentration, memory, and overall academic performance.